2019
DOI: 10.1002/jhbp.671
|View full text |Cite
|
Sign up to set email alerts
|

Upfront pancreaticoduodenectomy in severely jaundiced patients: is it safe?

Abstract: Aim The aim of this study was to evaluate the outcomes following upfront pancreaticoduodenectomy (PD) in severely jaundiced (serum bilirubin level ≥15 mg/dl) patients with malignant distal common bile duct (CBD) obstruction. Background Recent studies have failed to show the benefits of preoperative biliary drainage (PBD) before PD. In addition, there is limited data on the impact of upfront PD on perioperative outcomes in severely jaundiced patients. Methods We reviewed the prospectively collected data of 177 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The reduction in post-operative complications with DS is consistent with the findings of the Van der Gaag et al RCT that compared PBD to DS, where DS was found to lead to fewer complications (P< 0.001), less readmissions, and a shorter total LOS [10]. None of the aforementioned studies report a significant difference in post-operative mortality between the DS and PBD groups [7,10,12]. Likewise, the 2012 Cochrane review comparing PBD and DS that analyzed the findings of 6 RCTs found no significant difference in the rate of mortality or serious morbidity between the two intervention groups [13].…”
Section: Complication and Mortality Ratessupporting
confidence: 79%
See 2 more Smart Citations
“…The reduction in post-operative complications with DS is consistent with the findings of the Van der Gaag et al RCT that compared PBD to DS, where DS was found to lead to fewer complications (P< 0.001), less readmissions, and a shorter total LOS [10]. None of the aforementioned studies report a significant difference in post-operative mortality between the DS and PBD groups [7,10,12]. Likewise, the 2012 Cochrane review comparing PBD and DS that analyzed the findings of 6 RCTs found no significant difference in the rate of mortality or serious morbidity between the two intervention groups [13].…”
Section: Complication and Mortality Ratessupporting
confidence: 79%
“…However, there are at least two retrospective cohort studies of similar size, focusing on patients with a bilirubin of >250 µmol/L that predate this study. Pamecha et al [12], and Arkadopoulos et al [7] (Table 1) both demonstrate converse findings, with a significant reduction in overall and infective complication rates with DS. Similarly, De Pastena et al report a significantly reduced rate of infective complications including: abdominal collections (28.3% versus 35.9%; P= 0.001), sepsis (15.1% versus 24.1%; P= 0.001), and surgical site infections (SSIs) (5.4% versus 18.1%; P< 0.001) in the DS group of their large retrospective cohort study (n = 1,500) (Table 1) [8].…”
Section: Complication and Mortality Ratesmentioning
confidence: 88%
See 1 more Smart Citation
“…1 Additionally, a report described that pancreaticoduodenectomy could be safely performed in patients with severe jaundice without the need of EBD. 18 Whereas, in Japan, preoperative biliary drainage is commonly performed by EBD because preoperative detailed examinations such as positron emission tomography and systemic management are emphasized. 19 This strategy has been shown to be beneficial.…”
Section: T a B L E 2 Outcome Measuresmentioning
confidence: 99%
“…A study based on SEER database in USA showed that the utilization of preoperative biliary stent placement doubled from 1992 to 2007 [2]. However, since the 21st century, with the continuous progress of surgical technology and perioperative management, more and more studies have shown that PBD could not bene t the patients, on the contrary, it can increase the postoperative complications [3][4][5][6][7][8][9]. But in clinical practice, there are still many situations that patients need PBD due to different reasons.…”
Section: Introductionmentioning
confidence: 99%